UJI TOKSISITAS DAN PROFIL FTIR EKSTRAK METANOL SPONS Niphates olemda ASAL PULAU SAMALONA KEPULAUAN SPERMONDE (TOXICITY AND FTIR PROFILE OF SPONS METHANOL EXTRACT OF Niphates olemda FROM SAMALONA ISLANDS OF SPERMONDE ARCHIPELAGO) - Ajuk Sapar; Alfian Noor; Nunuk Hariani Soekamto; Ahyar Ahmad (Indonesian Journal of Pure and Applied Chemistry, 2020)
Preliminary research including toxicity testing, phytochemical test, and FTIR analysis of methanol extracts from sponge species Niphates olemda has been carried out. Small scale extraction was carried out on 23 g of the wet sponge sample using methanol and obtained as much as 40.3 mg of methanol extract. The results of the toxicity test using the BSLT method using Artemia salina showed that the Niphates olemda extract was toxic with LC50 value of 87.5 ppm.The phytochemical test results show that the methanol extract contains steroids and terpenoids. FTIR profile of methanol extract Niphates olemda indicated the presence of the main functional groups, namely C=O, OH, C=C, =CH, CH2, CH3, and C-O